Biological and Pharmacological Activity of Plant Natural Compounds - Pezzani, Raffaele; Vitalini, Sara (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Phytotherapy is probably the oldest form of medicine; however, it represents a new therapeutic tool for healthcare workers. Indeed plants are an infinite source of novel molecules, with countless possible combinations. This collection of articles (a Special Issue from Molecules) brings together the most up-to-date studies on the use of plant-derived compounds, ranging from their anti-inflammatory, antioxidant, and anticancer effects to the revision of the prominent literature.